Anti-infective Effects of a Fish-Derived Antimicrobial Peptide Against Drug-Resistant Bacteria and Its Synergistic Effects With Antibiotic - Chen, Yue; Wu, Jing; Cheng, Honglan; Dai, Yue; Wang, Yipeng; Yang, Hailong; Xiong, Fei; Xu, Wei; Wei, Lin (Frontiers in Microbiology, 2020)
Antimicrobial peptides (AMPs) play pivotal roles in protecting against microbial infection in fish. However, AMPs from topmouth culter (Erythroculter ilishaeformis) are rarely known. In our study, we isolated an AMP from the head kidney of topmouth culter, which belonged to liver-expressed antimicrobial peptide 2 (LEAP-2) family. Topmouth culter LEAP-2 showed inhibitory effects on aquatic bacterial growth, including antibiotic-resistant bacteria, with minimal inhibitory concentration (MIC) values ranging from 18.75 to 150 μg/ml. It was lethal for Aeromonas hydrophila (resistant to ampicillin), and took less than 60 min to kill A. hydrophila at concentration of 5×MIC. Scanning electron microscope (SEM) and SYTOX Green uptake assay indicated that it impaired the integrity of bacterial membrane by eliciting pore formation, thereby increased the permeabilization of bacterial membrane. In addition, it showed none inducible drug resistance to aquatic bacteria. Interestingly, it efficiently delayed ampicillin-induced drug resistance in Vibrio parahaemolyticus (sensitive to ampicillin), and sensitized ampicillin-resistant bacteria to ampicillin. Chequerboard assay indicated that topmouth culter LEAP-2 generated synergistic effects with ampicillin, indicating the combinational usage potential of topmouth culter LEAP-2 with antibiotics. As expected, topmouth culter LEAP-2 significantly alleviated ampicillin-resistant A. hydrophila infection in vivo, and enhanced the therapeutic efficacy of ampicillin against A. hydrophila in vivo. Our findings provides a fish innate immune system-derived peptide candidate for the substitute of antibiotics, and highlights its potential for application in antibiotic-resistant bacterial infection in aquaculture industry.